The Dysfunctional Dialectics of the Prison - Ball, Richard A. (1976)
According to the functionalist perspective, the survival of an organization is a matter of functions performed. A dialectical framework allows us to deal with the fact that durability is not necessarily connected with functionality. Organizations may be built on retrogressive accomodations which amount to dysfunctional dialectics. The prison represents an example in that it has developed as a polarity of commonweal and service organization, and is divided against itself. The coercive structure results in compliance patterns of an alienative nature. The basic dialectical units are roles which divide prisoners by emphasizing power relationships. Staff authority is weakened by a process of dialectical retrogressions. The prisoner subculture represents a dialectical defense against threats to individual self-images. The staff system will tend toward an organizational retrothesis made up of conflicting role realms of custody and treatment. Logical metacontrol possibilities include permanent external control, organizational revolution or abolition of the organization